СУЧАСНІ ЕЛЕКТРОІЗОЛЯЦІЙНІ МАТЕРІАЛИ ДЛЯ СИЛОВИХ КАБЕЛІВ ТА ЕЛЕКТРИЧНИХ ПРОВОДІВ - Щерба, А.А.; Кучерява, І.М. (Інститут електродинаміки Національної академії наук України, 2025)
The paper presents the review and substantive analysis on modern insulating materials for power cables and electrical wires. The state of the scientific-and-technical problem regarding the existing insulating materials, their selection according to electrical, thermal and ecological characteristics to ensure the reliable, safe and long-term operation of the cable and wire systems is described. The advantages and limitations of cross-linked polyethylene insulation are presented. Its up-to-date modification, tree-resistant cross-linked polyethylene, is described. The studies on the creation of promising nanocomposite and new environmentally friendly insulating materials are analyzed. The main direction of the studies is the improvement of the basic properties of polymers by adding the nano-sized particles and modifying the structure of the materials. Ref. 50, fig. 8, tables 5.